If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3(2x) = 39 Remove parenthesis around (2x) 7x + 3 * 2x = 39 Multiply 3 * 2 7x + 6x = 39 Combine like terms: 7x + 6x = 13x 13x = 39 Solving 13x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '13'. x = 3 Simplifying x = 3
| 4(2x-1)-2(3x+5)=x+4 | | 2/3+x^2-5/6+x=0 | | 12+d+8+4d= | | 2/3x^2-5/6x=0 | | 2/3x^2-5/6x | | 5/11x5/12 | | 2(1+5x)=82 | | 24=4x-10 | | 10(r-6)/10r | | -b+2=-.5 | | 5+9x=1+3x | | 6x+3x+x= | | 12y+6-11y=14.5 | | 8x+2x=40 | | 10=4a+10 | | 5/3x=1/x+2 | | 9h-15=75 | | (4+2x)2=2+-2 | | 2x/3+x/2=7/4+x | | -b+2=.5 | | -4*0+8y=-32 | | 3t^2-180=0 | | 3x/4=8+x/2 | | n-9=(-14) | | -3(1+8r)=117 | | 5k+7=13k-9 | | 48(2x-1)=8(x+5)+2 | | 0.25y-1.4y=0.15y+1-0.5y | | 12j-41+5j-17=180 | | 2(9x-7)+15x= | | 2x+(-6)=6 | | .25y-1.4=.15y-.5y |